CEACAM1 regulates CD8+ T cell immunity and protects from severe pathology during Citrobacter rodentium induced colitis. (1st November 2020) - Zöller, Julia; Ebel, Jana-Fabienne; Khairnar, Vishal; Schmitt, Verena; Klopfleisch, Robert; Meiners, Jana; Seiffart, Virginia; Hansen, Wiebke; Buer, Jan; Singer, Bernhard B.; Lang, Karl S.; Westendorf, Astrid M.
ABSTRACT: The incidence of gastrointestinal infections continues to increase, and infectious colitis contributes significantly to morbidity and mortality worldwide. Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) has been discovered to be strongly involved in the intestinal homeostasis. However, whether intestinal CEACAM1 expression has an impact on the control of infectious colitis remains elusive. Citrobacter rodentium (C. rodentium) is a gram-negative enteric pathogen that induces colonic inflammation in mice, with a critical role for CD4 + T cell but not CD8 + T cell immunity to primary infection. Here, we show that Ceacam1 −/− mice are much more susceptible to C. rodentium infection than wildtype mice, which is mediated by a defect in the intestinal barrier and, surprisingly, by a dysregulated CD8 + T cell but not CD4 + T cell response in the colon. CEACAM1 expression is essential for the control of CD8 + T cell immunity, as CEACAM1 deficiency during C. rodentium infection inhibits CD8 + T cell exhaustion. We conclude that CEACAM1 is an important regulator of CD8 + T cell function in the colon, and blocking CEACAM1 signaling to activate CD8 + T cells may have unforeseen side effects.